Pengaruh Latihan Skipping Terhadap Vertical Jump Atlet Bola Voli Di Ukm Bola Voli Putera Universitas Muhammadiyah Surakarta - AZIZA, Zelliana, Dwi Rosella K, S.St FT., M.Fis, Agus Widodo, S.Fis, M.Kes (2015)
Background : Vertical jump is a jump upright of vertical direction is done without prefix with arms reach its maximum height.One of the exercises that can improve vertical jump athletes are skipping exercise. Objective : To determine the effect of skipping exercise for vertical jump volleyball athletes in men volleyball Muhammadiyah University of Surakarta. Methods : The study was a quasi experiment with pre and post test with control group design, the sample in the treatment group was given skipping exercise for 4 weeks with a frequency of 3 times a week. Vertical jump measurements performed with vertical jump test using a midline parameters. Data analysis techniques using Wilcoxon test. Results : There were skipping exercise influence on the vertical jump athletes in men volleyball Muhammadiyah University of Surakarta after statistical test using Wilcoxon test obtained indigo Z -2.023 (p-value 0.008) in the treatment group and the obtained value of Z -2.668 (p Value-0.43) in the control group. Conclusion : There are skipping exercise influence on the vertical jum athletes in men volleyball Muhammadiyah University of Surakarta.